Preparation and characterization of SrFe12O19on optical and dielectric properties of Na2O-CaO-P2O5glasses - Pratthana Intawin (2018)
© 2016 Trans Tech Publications, Switzerland. In this research, the effects of SrFe12O19: SF on optical and dielectric properties of Na2O-CaO-P2O5glasses were investigated. From the study, the optically transparent glass, SF/Na2O-CaO-P2O5, system was successfully prepared by melt-quench method. The composition of SF/Na2O-CaO-P2O5used in this study are ranging between 5-20 wt.% SF. It was found that the addition of SF enhanced the conductivity, but in turn reduced the percentage of transmittance in the glasses. The glasses subjected to be adding SF contents at higher than 15 wt% were opaque, while the lower range gave highly transparent glass ceramics. The dielectric constant (ϵr) of the SF/Na2O-CaO-P2O5glasses were improved by increasing the content of SF, which in turn plays an important role in controlling the properties of the glass ceramics, including physical, optical, and dielectric properties.